Electronics, principles and applications / Charles A. Schuler - Schuler, Charles A. (1989)
Itroduction, a brief history , digital of analog, analog functions circuits wiith both dc and ac, trends in electronics; semiconductors, conductors, and insulators semiconductors, N-TYPe semiconductors, P-TYPe semiconductors majority and minority carriers: junction diodes, the PN junction, characteristic curver of diodes diode lead identification, diode types and applicacions; power supplies, the power-supply system, rectification, full-wave rectification, conversion of RMS values, filters voltage multiplera, ripple and regulators troubleshooting, replacement parts; junction transistors, amplification, transistrs, characteristic curves, transistor data, transistor testing, other transistor TYPes, transistors as switches; introduction to small-signal amplifiers, measuring gain, common- emitter amplifier, stabilizing the amplifier, other configuration simulation and models; more adout amall-signal amplifiera, amplifier couplinh, voltage gain in coupled stages, field- effect transistor amplifier, negative feedback, frequency response; large-signal amplifiers, amplifier class, class a power amplifiers class b power amplifiers, class ab power amplifiers class c power amplifiers swich- mode amplifiers; operational amplifiers, the differential amplifier diferetial amplifiers analysis, operational amplifiers setting op- amp gain, frequency effects in op amps, op- amp applications comparators; traubleshooting, distortion and noise, intermittents, operational amplifiers; oscillators, oscillator troubleshooting, direct digital synthesis, radio receiverrs, frequency modulation and, single sideband, receiver troubleshootiong; integrated circuits, additional digital signal processing, troubleshooting; electronic control devices and circuits, feedback in control circuitry, troubleshooting electronic; regulated power suptlies, current and voltege limiting, switch-mode regulators, troubleshooting regulated, power supplies.